OTORITAS HUKUM KELUARGA ISLAM DI KALANGAN PENGHULU KANTOR URUSAN AGAMA TERNATE DAN TIDORE - Abubakar, Fatum; Djakat, Muhrim; Ismail, Nining Zahara Ismail Zahara; Bicoli, Darwis U. (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2024)
This article analyzes the authority of Islamic family law among the heads of the Religious Affairs Office (KUA) in Ternate and Tidore, Indonesia. This research is a type of field research with qualitative methods. The research involved princes in the northern Maluku region consisting of the Sultanates of Ternate and Tidore. The research results show that the headman has coercive authority to force legal implementers (children or parents for parties who are getting married) to comply with existing rules because there is a legal basis which is the authority of the headman as the party registering the marriage. In dealing with legal authorities such as in determining marriage guardians, determining the period of 'iddah and pregnant marriages, the headmen in Ternate and Tidore generally use Fiqh legal considerations rather than state laws such as KHI and so on. This is because formal legislation issued by the state (such as KHI) does not have a negotiating nature and is final. Furthermore, alternatives for consideration of minimizing harm and taking the path to benefit are taken from the legal propositions of Fiqh.